The Extent of Practice of Critical Thinking Skills by Islamic Education Teachers in Saudi Arabia - Jamal Alkhaldi (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to reveal the extent of practice of critical thinking skills by Islamic Education Teachers  in Saudi Arabia from their point of view. To achieve this goal, the researcher followed a descriptive survey method, where he designed a questionnaire that consisted of (25) paragraphs. The questionnaire was distributed to (617) teachers in the Eastern Province of Saudi Arabia. The results of the study showed that the degree of practice of critical thinking skills by Islamic Education Teachers was moderate. In addition, there was a statistically significant difference in educational stage in favor of higher stages. Moreover, there was a statistically significant difference in the qualification variable in favor of postgraduate degrees. Finally, the results of the study pointed to a statistically significant difference in the teaching experience variable in favor of more experienced teachers. The study, thus, recommends holding training programs and courses that help teachers employ critical thinking skills in the classroom.